Elevated levels of markers of endothelial cell damage and markers of activated coagulation in patients with systemic necrotizing vasculitis - Hergesell, Olaf; Andrassy, Konrad; Nawroth, Peter Paul (Thrombosis and haemostasis, 1996)
Activation of coagulation and endothelial cell damage was studied in 47 patients with small vessel vasculitis [Wegener’s granulomatosis (WG) and microscopic polyangiitis (MP)] by measurement of throm-bin-antithrombin III complexes (TAT), fibrin-D-dimers (D-dimers), von Willebrand-factor (vWF) concentration and plasma thrombomodulin (TM) levels. There was a close correlation between disease activity (DA) in patients with WG or MP and markers of endothelial cell damage (correlation TM/DA r = 0.46 for WG and r = 0.43 for MP) and activated coagulation (correlation TAT/DA r = 0.58 for WG and r = 0.55 for MP). - - Elevation of the markers of activated haemostasis and endothelial cell damage was reversed when remission was obtained by specific treatment. The markers studied were particularly helpful in cases where measurement of antineutrophil cytoplasmatic antibodies (ANCA) did fail to assess disease activity.
Elektronische Reproduktion der Druck-Ausgabe 11. Juli 2018
Gesehen am 24.10.2023